Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Melakukan Pembayaran Pajak Bumi dan Bangunan di Kelurahan Bangunsari - Mary Zayyin Nabila Ulfa; Iin Wijayanti; Rizki Listyono Putro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Land and Building Tax is a crucial source of revenue in supporting the administration of government and regional development. Therefore, the level of taxpayer compliance in paying Land and Building Tax is a determining factor in optimizing regional tax revenue. This study aims to examine the effect of taxpayer awareness, tax knowledge, tax sanctions, socialization, income, and the quality of tax authority service on taxpayer compliance in Bangunsari Village. The object of this study is taxpayers registered in Bangunsari Village for the 2021-2025 period. The sample consists of 100 respondents determined using a purposive sampling technique with the Slovin formula. The data used are primary and secondary data, analyzed through Multiple Linear Regression with the help of SPSS version 24. The results show that taxpayer awareness, income, and the quality of tax authority service have a significant effect on taxpayer compliance, while tax knowledge, tax sanctions, and socialization have no significant effect on taxpayer compliance. Simultaneously, all independent variables affect the dependent variable with a determination value of 38.9%, while the remaining 61.1% is influenced by other factors.